Measuring the Contribution of Ecotourism Activities to Rural Economic Diversification and Long-Term Community Resilience - Tita Rosalina (Mandalika Journal of Business and Management Studies, 2025)
Ecotourism has become a strategic approach to achieving sustainable rural development by linking environmental conservation with local economic empowerment. This study aims to measure the contribution of ecotourism activities to rural economic diversification and long-term community resilience. Employing a qualitative research design through an extensive literature review, the study synthesizes data from peer-reviewed journals and international reports published within the last decade. Thematic and content analyses were conducted to identify mechanisms through which ecotourism influences local economies and social systems. Findings reveal that ecotourism significantly contributes to income generation, employment creation, and enterprise development, especially through community-managed homestays, nature-based tourism, and local crafts. Beyond its economic benefits, ecotourism strengthens institutional capacity, enhances social inclusion, and promotes environmental stewardship. It fosters adaptive skills and community-based governance that enhance resilience against socio-economic and environmental shocks. The study concludes that community-led, inclusive, and environmentally grounded ecotourism models provide the strongest foundations for sustainable rural development.